COMPOUND WORDS IN THE KERINCI LANGUAGE, PONDOK TINGGI DIALECT - Arif, Nely; Volya, Duty; ., Ernanda (Universitas Jambi, 2014)
This research focused on compound words inÂ the Kerinci language, Pondok Tinggi Dialect seen from its function in the sentence. To clarify the issues to be investigated, then the problem is formulated as âHow are the compound words in the Kerinci language, Pondok TinggiÂ dialect seen from its function in the sentence?â This research is descriptive qualitative. The sources of data in this research were the use of spoken language. This research is conducted because until now there is no written data source such as magazines, books and so on in the Kerinci language, Pondok Tinggi Dialect. The research involved several informants whose criteria refer to the opinion of Samarin (1998), Djajasudarma (1993), and Sudaryanto (1998).The data in this research were obtained by using the technique of observation, interviews and recordings. The function of the compound in Kerinci language, Pondok Tingi Dialect can grammatically be a subject, predicate, object, and adverbs. The pattern of formation of compound words are: Compound Words thatÂ Function As subject, e.g.: N + N, V + N and N + V;Â the function ofÂ compound word as a predicate , such as N + N , / Ba - / + N + N ; Compound words function as Object , some of them areÂ N + V / N, N + V / N / Adv; and function ofÂ compound word as adverb , some of them areÂ N + N , N + V , and N+R+N